Extensive Mycobacterium abscessus Pneumonia in an Immunocompetent Infant with No Underlying Lung Pathology - Morouge M. Alramadhan; James R. Murphy; Michael L. Chang (Case Reports in Infectious Diseases)
Pulmonary infection due to Mycobacterium abscessus occurs in patients with cystic fibrosis, but rarely in immunocompetent children without underlying lung pathology. Treatment is complicated by frequent resistance to many antibiotics. We present a case report of a 4-month-old female infant with 2 months of cough, difficulty feeding, and failure to thrive, with extensive culture-confirmed M. abscessus pulmonary infection without identified immunodeficiency or underlying lung pathology following multidisciplinary evaluation. We describe our complete evaluation including immunodeficiency evaluation incorporating whole-exome sequencing, describe our antibiotic selection and treatment duration given complicated susceptibility pattern of the M. abscessus isolate, and review literature for nontuberculous mycobacterial pulmonary disease in immunocompetent children. A complete multidisciplinary evaluation for underlying lung disease and primary and acquired immunodeficiency should be undertaken in pediatric patients with M. abscessus pneumonia. Confirming macrolide susceptibility through erm(41) gene evaluation is clinically important for isolates with complicated susceptibility pattern.